2018
DOI: 10.1002/aqc.2924
|View full text |Cite
|
Sign up to set email alerts
|

Integrating fishing and conservation in a risk framework: A stochastic population model to guide the proactive management of a threatened freshwater crayfish

Abstract: Numerous freshwater species are recreationally harvested, yet conservation concerns are often ignored. This may lead to conflict between fisheries and conservation management for a species. Approximately one‐third of freshwater crayfish species globally are threatened with extinction, including the Murray crayfish, Euastacus armatus (von Martens, 1866) in south‐eastern Australia. There has been substantial commercial and recreational fishing of E. armatus since European settlement, as well as other threats suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
(96 reference statements)
0
20
0
Order By: Relevance
“…Community engagement during the design and development of conservation and management approaches has tended to focus on issues and views from stakeholders who derive extractive (harvest) or non‐extractive (tourism) economic value from the species (Hesselink, Goldstein, van Kempen, Garnett, & Dela, ; MEA, ; Todd et al, ; United Nations Environment Programme (UNEP), ). An emerging body of literature has uncovered how aquatic species support complex cultural relationships and non‐economic values across different sectors of society, fitting the definition of a CKS (Cristancho & Vining, ; Garibaldi & Turner, ; Noble et al, ), the present study showed that E. armatus is an important part of the cultural identity of stakeholders across the MDB, who view the species as a social–ecological keystone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Community engagement during the design and development of conservation and management approaches has tended to focus on issues and views from stakeholders who derive extractive (harvest) or non‐extractive (tourism) economic value from the species (Hesselink, Goldstein, van Kempen, Garnett, & Dela, ; MEA, ; Todd et al, ; United Nations Environment Programme (UNEP), ). An emerging body of literature has uncovered how aquatic species support complex cultural relationships and non‐economic values across different sectors of society, fitting the definition of a CKS (Cristancho & Vining, ; Garibaldi & Turner, ; Noble et al, ), the present study showed that E. armatus is an important part of the cultural identity of stakeholders across the MDB, who view the species as a social–ecological keystone.…”
Section: Discussionmentioning
confidence: 99%
“…In response, relevant government jurisdictions have listed E. armatus as threatened, but have adopted varying approaches that range from full protection (in Australian Capital Territory and South Australia) to restricted recreational harvests (in New South Wales and Victoria). Although such regional declines in this freshwater crayfish may have had considerable social (Noble et al, ) and ecological implications for the affected regions, an understanding of these social impacts remains limited to fishing‐related aspects (Todd et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also important to highlight the numerous applied functions of models (e.g., for the management of invasions), which have been used in several contexts. Some examples are the management of emerging riverine invaders [51] and guiding proactive management of threatened freshwater crayfish [52]. Moreover, the local or regional management of invasive crayfish populations can be aided by population dynamics models and management models.…”
Section: Modelsmentioning
confidence: 99%